Study of strontium ferrites substituted by lanthanum on the structural and magnetic properties - Onreabroy,W. (Elsevier Limited, 2015)
M-type strontium ferrites, Sr 0.8La 0.2Fe 12O 19 have been synthesized by conventional ceramic process. The effects of lanthanum addition and sintering temperature on microstructures and magnetic properties of SrFe 12O 19 and Sr 0.8La 0.2Fe 12O 19 samples were investigated. Microstructural analysis of the SrFe 12O 19 and Sr 0.8La 0.2Fe 12O 19 specimens, sintered at different temperatures revealed that average grain sizes of SrFe 12O 19 ferrites were larger than that of Sr 0.8La 0.2Fe 12O 19 ferrite and increased with increasing sintering temperature. The X-ray diffraction (XRD) results confirmed the strontium hexagonal ferrite phase of SrFe 12O 19 and Sr 0.8La 0.2Fe 12O 19 compounds. A maximum coercivity value of 4850 Oe and maximum saturation magnetization value of 102 emu/g were obtained for the SrFe 12O 19 ferrite sintered at 1150°C and for the SrFe 12O 19 and Sr 0.8La 0.2Fe 12O 19 ferrites sintered at 1300°C, respectively. The remanence (Mr) of Sr 0.8La 0.2Fe 12O 19 sample sintered at 1200°C possesses the maximum value of 60 emu/g. © 2011 Elsevier Ltd and Techna Group S.r.l.